Chemical composition and therapeutic potential of three Cycas species in brain damage and pancreatitis provoked by γ-radiation exposure in rats. Issue 1 (1st January 2020) - Ismail, Ahmed; Hassan, Hossam M.; Moawad, Abeer S.; Abdel Fattah, Salma M.; Sherif, Noheir H.; Abdelmohsen, Usama R.; Radwan, Mohamed M.; Rateb, Mostafa E.; Hetta, Mona H.
ABSTRACT: Metabolomic profiling of the crude extracts of the three Cycas plants leaves; Cycas armstrongii Miq., Cycas circinalis L., and Cycas revoluta Thunb. showed the presence of diverse secondary metabolites. A detailed phytochemical study of C. armstrongii fractions led to isolation of 15 known components of different classes, but this is the first time to report them for this species. These components were chemically identified as (naringenin, dihydroamentoflavone, 2, 3-dihydrohinokiflavone, amentoflavone, 2, 3-dihydrobilobetin, isoginkgetin, prunin, naringin, vanillic acid, p- coumaric acid, β -sitosterol, stigmasterol, β -sitosterol glucoside, 3, 7, 9, 11-tetramethyl heptadecanoic acid, and N -(3ʹ-one-5ʹ-methyl)-hexyl-alanine). Moreover, the radioprotective potential of the three Cycas plant species was also investigated, and the ionizing radiation was performed by the exposure of rats whole-body to 8 Gy. The extracts of the three Cycas species were administered at a dose of 200 mg/kg each using an intra-gastric tube. Results indicated that Cycas spp. extracts significantly ameliorated radiation-induced brain and pancreatic damage as well as showing protection against radiation-induced oxidative stress. The results were also proved by histopathological study.